Poly (ADP-ribose) polymerase (PARP) as target for the treatment of epithelial ovarian cancer: what to know. (4th May 2021) - Della Corte, Luigi; Foreste, Virginia; Di Filippo, Claudia,; Giampaolino, Pierluigi; Bifulco, Giuseppe
ABSTRACT: Introduction: Poly (ADP-ribose) polymerase (PARP) inhibitors are being developed in maintenance and recurrence treatment settings of epithelial ovarian cancers (EOCs) with BRCA 1–2 gene mutation. PARP inhibitors are the first example of drugs targeting the loss of a gene suppressor: they block base-excision repair in the cancer cells, which have lost homologous recombination due to BRCA-mutation, resulting in loss of DNA repair and cell death, also known as synthetic lethality. Areas covered: This article provides an overview of PARP inhibitors in OC treatment and also an extensive section on the combined strategies of PARP inhibitors, including approved as well as currently investigated drugs. It also offers a section on the use of predictive biomarkers for PARP inhibitors treatment. Ongoing trials, including novel combinations, are discussed. Expert opinion: In recent years, there is increasing evidence that PARP inhibitor therapy can have life-long percussion in the treatment of EOC, even if some questions have to be solved yet, such as its use in combination therapy, the possibility to retreat with a PARP inhibitor, and finally how to overcome a resistance mechanism to this therapy. In this way, PARP inhibitors can obtain an important role in making a personalized therapeutic program in the case of first-line, neoadjuvant, platinum-sensitive, and resistant high-grade serous OC treatment.